The novel ginsenoside AD2 prevents angiotensin II-induced connexin 40 and connexin 43 dysregulation by activating AMP kinase signaling in perfused beating rat atria. (25th April 2021) - Li, Xiang; Cui, Xun; Zhou, Shuai; Xing, Da-lin; Piao, Hu-ri; Zhang, Qing-gao; Zhao, Yu-qing; Liu, Li-ping
Abstract: Connexin-40 (Cx40) and Cx43 are the principal components of gap junctions. Dysregulation of connexin expression is clinically related to cardiac pathologies. 25-Hydroxy protopanaxadiol [25-OH-PPD, 20 (R)-dammarane-3β, 12β, 20, 25-tetrol], known as AD2, is a novel protopanaxadiol extracted from Panax ginseng that exhibits many pharmacological activities, but its effects on cardiac gap junctions are poorly understood. The aim of this study was to evaluate the effects of AD2 on angiotensin II (Ang II)-induced Cx40 and Cx43 dysregulation. In this study, isolated beating rat atria were perfused with Ang II (5 μM) for 1 h to induce Cx40 and Cx43 dysregulation. The effects of AD2 (1.6, 16, and 160 μg/100 g body weight) on Ang II-induced hemodynamics in rats were analyzed by biological recorder, and changes in proteins levels were analyzed by western blotting. The results showed that AD2 ameliorated Ang II-induced hyper hemodynamics and abnormal P-waves, and prevented fibrotic collagen deposition (3.77% ± 1.64%–26.31% ± 1.64% with Ang II, 5.76% ± 0.94% with AD2). Ang II upregulated expression of nuclear factor kappa B, activator protein 1, and transforming growth factor β1, and downregulated of Cx40 and Cx43 expression, which were inhibited by AD2 concomitantly with increased of AMP-activated protein kinase (AMPK) expression via liver kinase B1 activation. The present findings suggest that AD2 inhibited Ang II-induced dysregulation of Cx40 and Cx43 via activation of AMPK signaling, thus highlighting the promise and utility of AD2 for treatment of connexin dysregulation-related heart disease. Highlights: AD2 ameliorated Ang II-induced hyper hemodynamics and abnormal P-waves in rats. AD2 prevented Ang II-induced atrial fibrosis by inhibition of TGF-β1. AD2 improved Ang II-induced Cx40 and Cx43 dysregulation via the LKB1-AMPK pathway. AD2 has therapeutic potential for preventing Ang II related connexin dysregulation.